2017
DOI: 10.1002/ajpa.23209
|View full text |Cite
|
Sign up to set email alerts
|

East of the Andes: The genetic profile of the Peruvian Amazon populations

Abstract: The Peruvian Amazon is home to an array of populations with differential rates of genetic exchanges with their neighbors and with the Andean people, depending on their peculiar demographic histories. We highlighted some successful Y chromosome lineages expansions originated in Peru during the pre-Columbian history which involved both Andeans and Amazon Arawak people, showing that at least a part of the Amazon rainforest did not remain isolated from those exchanges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
5
20
0
Order By: Relevance
“…Hints from uniparental markers suggested that some gene flow between the Andes and Amazon could have occurred (Barbieri et al. 2014; Di Corcia et al. 2017; Gómez-Carballa et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hints from uniparental markers suggested that some gene flow between the Andes and Amazon could have occurred (Barbieri et al. 2014; Di Corcia et al. 2017; Gómez-Carballa et al.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage from samples previously typed for uniparental markers, we generated new genomic data for five ethnic groups from Peruvian Amazon (Barbieri et al. 2014; Di Corcia et al. 2017), one group from the Gran Chaco region (Sevini et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results of clustering of STR profiles obtained by DAPC were compared with those from mtDNA analysis. mtDNAs of 132 urban Peruvian and 10 Moche individuals were newly genotyped, while the haplotypes of the remaining 90 Native Amazons were already available [ 15 ]. In S1 Table , for each subject, the variants of mtDNA HVS-I, HVS-II and coding regions are listed, along with the haplogroup and STR cluster affiliations.…”
Section: Resultsmentioning
confidence: 99%
“…The mtDNA of 132 urban Peruvian samples and 10 Native Amazon individuals belonging to Moche population were analyzed by sequencing, while mtDNA haplotypes of the other Native individuals were already published [ 15 ]. The amplification of the first and second hypervariable segments (HVS-I and HVS-II) of the mtDNA control region was carried out in a 25 μl reaction volume under standard conditions [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation